2001
DOI: 10.1177/107906320101300403
|View full text |Cite
|
Sign up to set email alerts
|

Hostility Toward Women and Victim Empathy in Rapists

Abstract: The present study examined empathy and hostility toward women among 32 rapists, 28 nonsex offenders, and 40 nonoffender males. Results indicated that rapists were significantly less empathic than either of the other two groups toward women who had been sexually assaulted by an unknown assailant. They were also significantly less empathic toward their own victims than toward any other women, and they were markedly more hostile toward women than were the other subjects. Finally, among the rapists, hostility towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 16 publications
(11 reference statements)
3
37
0
3
Order By: Relevance
“…[7][8][9] Such rapes occur when the male suspects his partner's fidelity. Research on Convicted Rapists: Apart from the factors listed above, other factors include 10,11 1. An exaggerated sense of masculinity which is often gratified/ satisfied only through coercive sex/ forced sex.…”
Section: Types Of Rapementioning
confidence: 99%
“…[7][8][9] Such rapes occur when the male suspects his partner's fidelity. Research on Convicted Rapists: Apart from the factors listed above, other factors include 10,11 1. An exaggerated sense of masculinity which is often gratified/ satisfied only through coercive sex/ forced sex.…”
Section: Types Of Rapementioning
confidence: 99%
“…Convicted male rapists have indicated greater hostility toward women than male non-sexual offenders (Marshall & Moulden, 2001), and among male university students, hostility toward women is more strongly related to sexual coercion than other types of attitudes about women (e.g., sexism) and attitudes about sexual assault (e.g., rape myth acceptance; Forbes et al, 2004). Further, the results of a meta-analysis of 39 studies relating masculine ideology to sexual aggression found that hostile masculinity was most robustly associated with sexual aggression among numerous other predictors, including power over women, hypermasculinity, rape myth acceptance, attitudes toward women's rights, adversarial sexual beliefs, sex role conservatism, and sex role stereotyping (Murnen et al, 2002).…”
Section: Hostility Toward Womenmentioning
confidence: 99%
“…A lack of empathy for victims in particular, as opposed to a lack of empathy in general, is related to sexual assault and sexual harassment perpetration (Marshall et al, 1995;Marshall & Moulden, 2001;Quinn, 2002). For instance, compared to incarcerated male nonsexual offenders, sexual offenders displayed the least amount of empathy toward their victim's but displayed an equal amount of empathy as nonsexual offenders toward an unknown female victim of sexual assault (Fernandez & Marshall, 2003).…”
Section: Offender Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors include belief in rape myths (Lonsway & Fitzgerald, 1994), victim-blaming attitudes (Maxwell, Robinson, & Post, 2003), hostility toward women (Marshall & Moulden, 2001), exposure to sexually explicit media (Vega & Malamuth, 2007), deviant sexual fantasies (Malamuth et al, 1995), and perceived peer support for forced sex (Abbey et al, 2007). Some of these factors have been addressed frequently by SV prevention programs (e.g., belief in rape myths, victim-blaming attitudes), and others are considered most often in treatment settings (e.g., deviant sexual fantasies).…”
Section: Risk Factors Unique To Sexual Violence Perpetrationmentioning
confidence: 99%